2015
DOI: 10.1094/pdis-07-14-0782-re
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide Resistance in Cercospora kikuchii, a Soybean Pathogen

Abstract: Isolates of Cercospora kikuchii, a soybean (Glycine max) pathogen causing Cercospora leaf blight and purple seed stain, were tested to determine baseline sensitivities (n = 50) to selected quinone outside inhibitor (QoI) fungicides by conducting radial growth assays on fungicide-amended media. Baseline effective fungicide concentration to inhibit 50% of fungal radial growth (EC50) values were compared with EC50 values for isolates collected in 2011 (n = 50), 2012 (n = 50), and 2013 (n = 36) throughout soybean-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 34 publications
5
50
1
3
Order By: Relevance
“…These EC 50 values are more likely to occur biologically and are similar to previous reports from the literature (Price et al 2015;Batzer et al 2016). In the present study, for two of the three fungi analyzed (C. kikuchii and P. phaseoli), the W1.4 model provided the lowest EC 50 .…”
supporting
confidence: 90%
See 1 more Smart Citation
“…These EC 50 values are more likely to occur biologically and are similar to previous reports from the literature (Price et al 2015;Batzer et al 2016). In the present study, for two of the three fungi analyzed (C. kikuchii and P. phaseoli), the W1.4 model provided the lowest EC 50 .…”
supporting
confidence: 90%
“…It is necessary to create a fungicide sensitivity-testing program in Argentina due to the numerous cases of fungicide resistance that have been already reported worldwide in soybean. In the United States, C. kikuchii isolates exhibiting multiple resistance to QoI and benzimidazole fungicides have already been confirmed and reported (Price et al 2015).…”
mentioning
confidence: 93%
“…However, disease management failures in legume crops associated with fungicide resistance have been reported from several countries (Chang et al, 2007;Lonergan et al, 2015;Price et al, 2015). For example, Price et al (2015) reported that isolates of C. kikuchii (Cercospora leaf spot) from soybean fields in Louisiana State, USA were insensitive to thiophanate methyl.…”
Section: Protection With Synthetic Fungicidesmentioning
confidence: 99%
“…However, disease management failures in legume crops associated with fungicide resistance have been reported from several countries (Chang et al, 2007;Lonergan et al, 2015;Price et al, 2015). For example, Price et al (2015) reported that isolates of C. kikuchii (Cercospora leaf spot) from soybean fields in Louisiana State, USA were insensitive to thiophanate methyl. Isolates of Ascochyta rabiei (ascochyta blight of chickpea) from Canada and USA showed insensitivity with fungicides pyraclostrobin, chlorothalonil, fluxapyroxad, and prothioconazole (Chang et al, 2007;Lonergan et al, 2015).…”
Section: Protection With Synthetic Fungicidesmentioning
confidence: 99%
See 1 more Smart Citation